Ultrasonographic guided botulinum toxin type A treatment for plantar fasciitis; an outcome-based investigation for treating pain and gait changes - Huang, YC; Wei, SH; Wang, HK; Lieu, FK (Journal of rehabilitation medicine, 2010)
To evaluate the effectiveness of ultrasonographic guided botulinum toxin type A injections into the plantar fascia to reduce pain and improve gait in patients with unilateral plantar fasciitis. A randomized double-blind control study. Fifty patients with chronic unilateral plantar fasciitis were recruited, and divided into experimental and control groups. Subjects in the experimental group were injected with 50 units botulinum toxin type A, reconstituted with normal saline, into the plantar fascia under ultrasonographic guidance. Follow-up evaluations were made 3 weeks and 3 months after injection. The control group subjects were injected with normal saline under ultrasonographic guidance. Outcome measures included comparing scores from the visual analogue pain scale, changes in thickness of the plantar fascia and fat pad, and gait assessment including the maximal centre of pressure velocity during first step loading response. Visual analogue pain scale and plantar fascia thickness in the symptomatic foot decreased significantly, as noted at follow-up 3 weeks and 3 months after botulinum toxin type A injections (p < 0.001). However, the fat pad thickness remained unchanged. The centre of pressure velocity during loading response increased 3 months after injection (p < 0.05). Outcome measures of the control group remained unchanged. Botulinum toxin type A is effective in the treatment of foot pain associated with plantar fasciitis and increases the centre of pressure velocity during loading response without inducing fat pad atrophy.